Management of psychological distress in adolescents through cognitive-behavioral group therapy - Hafizah, Nurul; Sulistyarini, RR. Indahria; Azkiya, Wafiq Natasya (Universitas Ahmad Dahlan, 2025)
Psychological distress among adolescents is increasingly widespread and is characterized by symptoms of anxiety, depression, and stress. Academic pressure, complex social dynamics, and exposure to digital media are considered key triggers. Psychological distress can disrupt development, lower academic achievement, and potentially lead to more serious mental disorders in adulthood. This study aims to examine the effectiveness of group cognitive behavioral therapy (CBT) for adolescents with psychological disorders. The research employed a quantitative quasi-experimental design with a one-group pretest-posttest design, without a control group. Participants consisted of eight adolescents, all aged 13, who experienced psychological distress. Psychological assessment procedures included interviews, behavioral observations, and the Kessler Psychological Distress Scale-10 (K-10), which was used to assess subjects' baseline psychological distress. The stages of the CBT group intervention included orienting the patients, identifying maladaptive thoughts and beliefs, challenging these maladaptive thoughts and beliefs, behavioral activation, problem-solving, and relaxation techniques. Data were analyzed using a dependent-samples t-test to assess changes in psychological distress, along with an analysis of interview data comparing participants' narratives before and after the intervention. The findings revealed a significant reduction in psychological distress scores, with participants demonstrating positive changes in thoughts, emotions, and behaviors, particularly in themes related to academic achievement, social issues, and family dynamics. The study suggests that CBT group therapy can serve as a practical psychological support strategy within the community to promote improved mental health among adolescents. Future research should include control groups to enhance the generalizability of the findings.